2015
DOI: 10.1016/j.jval.2015.03.1214
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Patient-Reported Outcome Measures In Registered Clinical Trials: Evidence From Clinicaltrials.Gov (2007-2013)

Abstract: A209OBJECTIVES: Decisions on palliative chemotherapy (CT) for advanced gastric cancer require trade-offs between potential benefits and risks for patients. Healthcare providers and payers agreed that patient preferences should be considered. We conducted a CBC study in patients with mGC or mGEJ-Ca from Germany to evaluate their preferences when trading-off between treatment tolerability, quality of life and survival benefit. METHODS: German oncologists were contacted to identify patients with mGC or mGEJ-Ca wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(37 citation statements)
references
References 24 publications
0
36
0
1
Order By: Relevance
“…On the other hand, PROs refer to a patient's subjective evaluation and satisfaction with treatment in terms of the patient's daily life. Consequently, PROs remain a high‐priority subject in relation to cancer patients and are increasingly recognized as an important component to achieve the paradigm of personalized medicine, not only in routine clinical practice, but also in clinical cancer trials . Among the PROs, symptom burden is one of the most relevant dimensions with respect to HRQOL in patients with mCRC .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PROs refer to a patient's subjective evaluation and satisfaction with treatment in terms of the patient's daily life. Consequently, PROs remain a high‐priority subject in relation to cancer patients and are increasingly recognized as an important component to achieve the paradigm of personalized medicine, not only in routine clinical practice, but also in clinical cancer trials . Among the PROs, symptom burden is one of the most relevant dimensions with respect to HRQOL in patients with mCRC .…”
Section: Discussionmentioning
confidence: 99%
“…Health‐related quality of life (HRQoL) and other Patient Reported Outcomes (PRO) have become increasingly used as endpoints in clinical cancer studies to measure patient‐experienced benefits and toxicities of treatments (Vodicka et al , ; Basch et al , ). PRO results are important in the approval of new drugs, as well as in shared decision‐making in the daily care of patients (Speight & Barendse, ; European Medicine Agency, ).…”
mentioning
confidence: 99%
“…They consider information from the patient's perspective essential to support a patientcentered approach to care. A survey of nearly 100,000 clinical trials published between 2007 and 2013 found that a PROM was used in 27% of these trials [4]. For older adults, PROMs are specifically important because they may also be a means to express the patients' actual and desired quality of wellbeing.…”
Section: Introductionmentioning
confidence: 99%